Knowledge mapping of targeted immunotherapy for myasthenia gravis from 1998 to 2022: A bibliometric analysis - Su, Yue; Ruan, Zhe; Wang, Rui; Hao, Sijia; Tang, Yonglan; Huang, Xiaoxi; Gao, Ting; Li, Zhuyi; Chang, Ting (Frontiers in Immunology, 2022)
Background: The treatment of myasthenia gravis (MG) has gradually from steroids and traditional immunosuppressants to targeted immunotherapy. Targeted immunotherapy has been applied in the clinic and recognized as the most promising treatment recently. The aim of this study was to identify emerging trends and summarize the knowledge structure related to targeted immunotherapy for MG through bibliometric methods. Methods: We selected the Web of Science Core Collection database (WoSCC) to retrieve the literature on targeted immunotherapy for MG. VOSviewer and CiteSpace, two bibliometric analysis software and bibliometric online platform, are mainly used to evaluate the contribution and co-occurrence relationship of countries/regions, institutions, journals and authors and to determine future research hotspots and development trends, R 4.1.2 and Microsoft Excel 365 are used for statistical analysis. Results: A total of 824 papers were included in the analysis, including 562 original articles and 262 reviews. The number of publications on targeted immunotherapy for MG can be divided into two stages. The first stage showed a steady growth trend from 1998 to 2016, with an annual number of no more than 35 publications. The second stage showed an explosive growth trend since 2017, reaching a peak in 2020. The United States ranks first in the number of publications, citations and h-index in this field, maintaining a leading edge. The author with the highest citation and h-index is Vincent A. About 28.03% of the articles are published in the top 10 journals. The highest number of related articles were published in the Journal of Neuroimmunology, with an impact factor of 3.478. Among the top 10 cited articles, there are 6 reviews and 4 clinical studies. In addition to “myasthenia gravis”, the keyword with the highest attention is “rituximab”, followed by “double-blind”. Conclusion: The current study has summarized the global research trends concerning targeted immunotherapy for MG. Research hotpots gradually turned from basic research to clinical research over time. MG treatment has entered a personalized precision treatment phase. Further investigation into new targets and conducting high-quality randomized controlled trials on existing biological agents need to be addressed urgently, which are the future directions of immunotherapy research.